Low-carbon biodegradable metal working fluid

Through component screening and formulation compatibility research, a low-carbon biodegradable metal processing liquid was developed, which solved the problems of large carbon displacement, low degradation rate and poor environmental protection of the existing metal processing liquid, and achieved good lubricity, easy biodegradation, and environmentally friendly and low-carbon effects.

CN119899724AActive Publication Date: 2025-04-29KNC-DAISHIN LAB CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411919874.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-29
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Due to the development of mineral oil-based metal processing liquid, the carbon displacement is large, the degradation rate is low, the environmental protection is poor, the lubricity is poor, the consumption is large, and the content is harmful to the environment and water.

Method used

Through component screening and formulation compatibility research, a low-carbon biodegradable metal processing liquid was developed, using isopropanolamine, nanosilicon corrosion agent, tricarboxylic acid anti-rust agent, benzotriazole, 182 self-emulsified ester, ricinoleic acid, DOTP, Gerbert alcohol, ether carboxylic acid compound agent, and cashew phenol polyoxyethylene ether as the main components to replace traditional mineral oils and non-degradable emulsifiers.

Benefits of technology

The low-carbon biodegradable metal processing liquid has good lubricity and is easy to biodegradate, and has an increase in degradation rate by 80%. It is environmentally friendly and low-carbon, has good stability, can meet processing needs at low concentrations, save costs, and does not contain harmful substances, which is human and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207701840000071
    Figure BDA0005207701840000071
Patent Text Reader

Abstract

The invention belongs to the technical field of metal working fluids, and discloses a low-carbon biodegradable metal working fluid which comprises a low-carbon biodegradable metal working fluid. The cutting fluid comprises the following components in percentage by mass: 4%-6% of isopropanolamine, 1%-3% of a nano silicon anticorrosive agent, 2%-5% of a tricarboxylic acid antirust agent, 0.5%-2.5% of benzotriazole, 5%-10% of 182 self-emulsifying ester, 4%-6% of ricinoleic acid, 40%-60% of DOTP, 4%-8% of Guerbet alcohol, 2%-4% of an ether carboxylic acid compounding agent and the balance of water. The cleaning agent comprises the following components in percentage by weight: 2-5% of anacardol polyoxyethylene ether 5EO, 4-8% of anacardol polyoxyethylene ether 2EO, 0.4-0.6% of potassium hydroxide and the balance of water. The low-carbon biodegradable metal working fluid does not contain harmful substances, has excellent environmental protection performance and good lubricity, can be applied to processing of metals such as copper, aluminum and alloys thereof, magnesium and alloys thereof, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metalworking fluids, and in particular relates to a low-carbon biodegradable metalworking fluid. Background Art

[0002] Existing metalworking fluids (metalworking protective fluids) are mostly developed using mineral oil as the base. The development and refining process of mineral oil produces a large amount of carbon emissions, and the degradation rate is less than 20%. It is not easy to biodegrade and has poor environmental protection. Mineral oil sources are relatively scarce, non-renewable, and have poor lubricity, high consumption, and contain harmful substances. It poses great harm to the environment and water bodies. There is an urgent need to develop low-carbon and environmentally friendly metalworking fluids.

[0003] Using rapeseed oil and other vegetable oils to replace mineral oils to prepare metalworking fluids has become a way to develop low-carbon and environmentally friendly metalworking fluids. However, rapeseed oil and other vegetable oils have disadvantages such as easy oxidation, easy deterioration, and short life during use. They cannot truly replace mineral oils to achieve the various properties of metalworking fluids and reduce carbon emissions. In addition, most of the emulsifiers in existing metalworking fluids are fatty alcohol polyoxyethylene ethers, which are also not completely biodegradable. It is still necessary to comprehensively evaluate the various components and compatibility issues of metalworking fluids, develop low-carbon biodegradable metalworking fluids, and provide the market with a low-carbon and environmentally friendly low-carbon biodegradable metalworking fluid with stable performance. Summary of the invention

[0004] In order to solve the above technical problems, the present invention has developed a low-carbon biodegradable metalworking fluid through component screening and formula compatibility research. The metalworking fluid has good lubricity and is easily biodegradable.

[0005] On the one hand, the present invention provides a low-carbon biodegradable metalworking fluid, wherein the components of the low-carbon biodegradable metalworking fluid are, by mass percentage, 4%-6% of isopropanolamine, 1%-3% of nano-silicon corrosion inhibitor, 2%-5% of tricarboxylic acid rust inhibitor, 0.5%-2.5% of benzotriazole, 5%-10% of 182 self-emulsifying ester, 4%-6% of ricinoleic acid, 40%-60% of DOTP, 4%-8% of Guerbet alcohol, 2%-4% of ether carboxylic acid compounding agent, 2%-5% of cardanol polyoxyethylene ether 5EO, 4%-8% of cardanol polyoxyethylene ether 2EO, 0.4%-0.6% of potassium hydroxide, and the balance is water.

[0006] Furthermore, the low-carbon biodegradable metalworking fluid comprises, by mass percentage, 5% of isopropanolamine, 2% of nano-silicon corrosion inhibitor, 3% of tricarboxylic acid rust inhibitor, 1% of benzotriazole, 8% of 182 self-emulsifying ester, 5% of ricinoleic acid, 50% of DOTP, 6% of Guerbet alcohol, 3% of ether carboxylic acid compounding agent, 3% of cardanol polyoxyethylene ether 5EO, 5% of cardanol polyoxyethylene ether 2EO, 0.5% of potassium hydroxide, and the balance is water.

[0007] On the other hand, the present invention provides a method for preparing the low-carbon biodegradable metalworking fluid, the method for preparing the low-carbon biodegradable metalworking fluid comprising the following steps:

[0008] Step 1: Weigh each component of the low-carbon biodegradable metalworking fluid according to its mass percentage.

[0009] Step 2: Add water, isopropanolamine, tribasic acid, benzotriazole and potassium hydroxide into a 250 mL beaker and stir at room temperature until uniform and transparent.

[0010] Step 3: Add nano-silicon corrosion inhibitor, 182 self-emulsifying ester, ricinoleic acid, DOTP, Guerbet alcohol, ether carboxylic acid compounding agent, cardanol polyoxyethylene ether 5EO, and cardanol polyoxyethylene ether 2EO to the uniform transparent liquid prepared in step 2, and stir at 40° C. until it becomes uniform and transparent.

[0011] In addition, the present invention provides application of the low-carbon biodegradable metalworking fluid in metalworking, wherein the metal is copper, aluminum and its alloy, magnesium and its alloy.

[0012] Compared with the prior art, the present invention has at least the following advantages or beneficial effects:

[0013] The invention obtains a low-carbon biodegradable metalworking fluid by screening a large number of formula components and formula research and development. The low-carbon biodegradable metalworking fluid comprises, by mass percentage, 4%-6% of isopropanolamine, 1%-3% of nano silicon corrosion inhibitor, 2%-5% of tricarboxylic acid rust inhibitor, 0.5%-2.5% of benzotriazole, 5%-10% of 182 self-emulsifying ester, 4%-6% of ricinoleic acid, 40%-60% of DOTP, 4%-8% of Guerbet alcohol, 2%-4% of ether carboxylic acid compounding agent, 2%-5% of cardanol polyoxyethylene ether 5EO, 4%-8% of cardanol polyoxyethylene ether 2EO, 0.4%-0.6% of potassium hydroxide, and the balance is water. The low-carbon biodegradable metalworking fluid does not contain mineral oil and other harmful substances. The degradation rate of the DOTP used is 100%, which is 80% higher than that of mineral oil, and is environmentally friendly and low-carbon. The low-carbon biodegradable metalworking fluid uses an emulsifier, cardanol polyoxyethylene ether, to replace the original non-degradable high-grade fatty alcohol emulsifier, which greatly increases the degradation rate of the product. The low-carbon biodegradable metalworking fluid is stable and has good lubricity, which prolongs the life of the tool. The low-carbon concentration can also meet the processing requirements. The low-carbon metalworking fluid with a concentration of 4wt% can achieve the lubricity of the existing metalworking fluid with a concentration of 8wt%-10wt%, which greatly saves costs. The low-carbon biodegradable metalworking fluid does not contain Harmful substances, such as formaldehyde, dicyclohexylamine, nitrite, phenol and phenol-based fungicides and VOC volatile substances, are friendly to people; the low-carbon biodegradable metalworking fluid has good metal protection and can meet the processing of a variety of different materials at the same time; the low-carbon biodegradable metalworking fluid does not damage the paint and is compatible with commonly used machine tool sealing parts; the low-carbon biodegradable metalworking fluid product has low viscosity and good filterability, which can reduce the amount of coolant carried out, while keeping the tools and workpieces clean and saving costs; the low-carbon biodegradable metalworking fluid does not use mineral oil, but uses DOTP as the main raw material. A large amount of smoke and oil mist will not be generated during the processing, keeping the workshop clean and odor-free, and is operator-friendly. DETAILED DESCRIPTION

[0014] The technical solution of the present invention is described below in conjunction with embodiments; however, the present invention is not limited to the following embodiments.

[0015] The experimental methods and detection methods in the following embodiments are all conventional methods unless otherwise specified; the raw materials and materials are all commercially available unless otherwise specified; the index data are all conventional measurement methods unless otherwise specified.

[0016] Biodegradation: Biodegradation means that materials can be digested and metabolized by microorganisms existing in nature and decomposed into carbon dioxide, water and intermediates.

[0017] Low carbon: refers to the main raw materials of metalworking fluids. From the production process to the degradation of raw materials, the total carbon dioxide consumption is low.

[0018] High content: It does not contain mineral oil, but can still achieve the original cutting fluid content, and the cost performance remains unchanged.

[0019] Isopropanolamine: Isopropanolamine is an important corrosion inhibitor that can be used in boiler water treatment, automobile engine coolant, drilling and cutting oil and other types of lubricants to inhibit corrosion.

[0020] Nano silicon corrosion inhibitor: can be used for metal cleaning and cutting fluids. It is used as an anti-corrosion agent in metalworking lubricants for aluminum, magnesium, zinc and other metals. It also has very good lubrication and extreme pressure properties. Nano silicon corrosion inhibitor is used in water-soluble formulas. It is easy to operate and can be directly added to the concentrate without adding coupling agents. Metalworking fluid users can use it directly to improve the performance of the working fluid. Nano silicon corrosion inhibitor is most effective for the surface treatment of metal aluminum, especially in the treatment of many sensitive aviation aluminum alloys. It also has a corrosion inhibition effect on magnesium. This product is suitable for a variety of water qualities.

[0021] Ternary carboxylic acid rust inhibitor: It has good rust resistance, extremely low foaming property, good hard water stability, and the solution in the commonly used concentration range is non-irritating to the skin and mucous membranes. It is mainly used as a metal corrosion inhibitor additive in semi-synthetic cutting fluid, fully synthetic grinding fluid, water-based quenching fluid and water-based cleaning agent, automotive antifreeze, rust-proof water and other water-based products.

[0022] Benzotriazole: Mainly used as water treatment agent, metal rust preventer and corrosion inhibitor. Widely used in circulating water treatment agent, anti-rust oil, lipid products, also used in copper and copper alloy vapor phase corrosion inhibitor, lubricant additives. Used for surface purification of silver, copper, zinc in electroplating, it has anti-discoloration effect. BTA forms covalent bonds and coordination bonds with copper atoms, and replaces each other to form chain polymers, forming a multi-layer protective film on the surface of copper, so that the copper surface does not undergo redox reaction, does not generate hydrogen, and has an anti-corrosion effect. It also has the same effect on metal materials such as lead, cast iron, nickel, zinc, etc. BTA can be combined with a variety of corrosion inhibitors to improve the corrosion inhibition effect.

[0023] 182 Self-emulsifying ester: It is an ashless high molecular weight ester lubricant. It is widely used in metalworking fluids and industrial lubricants. Since it does not contain chlorine, sulfur, or phosphorus, it can replace chlorine- and sulfur-containing extreme pressure additives in soluble oils and semi-synthetic products; this synthetic ester product also has good hydrolysis stability.

[0024] Ricinoleic acid: mainly used as an emulsifier, auxiliary lubrication. It is an unsaturated fatty acid and has better anti-corruption properties than oleic acid.

[0025] DOTP (Dioctyl terephthalate): Molecular formula: C24H38O4 is a primary plasticizer with excellent performance for polyvinyl chloride (PVC) plastics. It has the advantages of heat resistance, cold resistance, low volatility, anti-extraction, flexibility and good electrical insulation performance. It can be used as a lubricant in metalworking fluids.

[0026] Guerbet alcohol: Guerbet alcohol is a general term for a class of fatty alcohols with a branched chain on the second carbon, also known as 2-alkyl-1-alkanol, which is a class of saturated primary alcohols. Due to the special structure of two 100% linear alkyl chains, it has the following characteristics: 1) low volatility; 2) low irritation; 3) low freezing point; 4) excellent lubricity; 5) excellent oxidation stability; 6) good solubility and dissolving power; 7) low viscosity; 8) good biodegradability.

[0027] Ether carboxylic acid compound: excellent resistance to hard water, chelates with Ca2+, Mg2+ in water, and the generated chelates have good dispersing effect; low foaming performance, the liquid will not produce a lot of foam; environmentally friendly, low toxicity, and has excellent biodegradability.

[0028] Potassium hydroxide: improves the reaction activity. Since most metalworking fluids are organic acid-base reactions with weak reaction activity, they need to be catalyzed and activated. Adding potassium hydroxide can improve the reaction activity of fatty acids and alcohol amines in cutting fluids and improve efficiency. It can increase the alkalinity value and reduce the amount of alkali. Activate hard water, and the hydroxide combines with calcium and magnesium in the water to form fine particle precipitation, which prevents fatty acids from combining with calcium and magnesium to form flocculent precipitation.

[0029] Cardanol polyoxyethylene ether 5EO: Cardanol is made from natural cashew nut shell oil, refined by advanced technology, and is a green and environmentally friendly industrial raw material. Because of its low price, abundant sources, excellent performance, and renewability, it is then synthesized and refined to become a surfactant, which is cost-effective.

[0030] Cardanol polyoxyethylene ether 2EO: Cardanol is made from natural cashew nut shell oil, refined by advanced technology, and is a green and environmentally friendly industrial raw material. Because of its low price, abundant sources, excellent performance, and renewability, it is then synthesized and refined to become a surfactant, which is cost-effective.

[0031] Example 1

[0032] This embodiment is to prepare a low-carbon biodegradable metalworking fluid.

[0033] 4% of isopropanolamine, 1% of nano-silicon corrosion inhibitor, 2% of tricarboxylic acid rust inhibitor, 0.5% of benzotriazole, 5% of 182 self-emulsifying ester, 4% of ricinoleic acid, 40% of DOTP, 4% of Guerbet alcohol, 2% of ether carboxylic acid compounding agent, 2% of cardanol polyoxyethylene ether 5EO, 4% of cardanol polyoxyethylene ether 2EO, 0.4% of potassium hydroxide, and the balance is water, are weighed in percentage by mass.

[0034] Add water, isopropanolamine, tribasic acid, benzotriazole and potassium hydroxide into a 250ml beaker according to the above proportions, and stir at room temperature until it is uniform and transparent. Then add nano silicon corrosion inhibitor, 182 self-emulsifying ester, ricinoleic acid, DOTP, Guerbet alcohol, ether carboxylic acid compounding agent, cardanol polyoxyethylene ether 5EO and cardanol polyoxyethylene ether 2EO to the above uniform and transparent liquid, and stir at 40°C until it is uniform and transparent to obtain a low-carbon biodegradable metalworking fluid. Mark it as 1# low-carbon biodegradable metalworking fluid for standby use.

[0035] Example 2

[0036] This embodiment is to prepare a low-carbon biodegradable metalworking fluid.

[0037] In percentage by mass, weigh 5% of isopropanolamine, 2% of nano-silicon corrosion inhibitor, 3% of tricarboxylic acid rust inhibitor, 1% of benzotriazole, 8% of 182 self-emulsifying ester, 5% of ricinoleic acid, 50% of DOTP, 6% of Guerbet alcohol, 3% of ether carboxylic acid compounding agent, 3% of cardanol polyoxyethylene ether 5EO, 5% of cardanol polyoxyethylene ether 2EO, 0.5% of potassium hydroxide, and the balance is water.

[0038] Add water, isopropanolamine, tribasic acid, benzotriazole and potassium hydroxide into a 250ml beaker according to the above proportions, and stir at room temperature until it is uniform and transparent. Then add nano silicon corrosion inhibitor, 182 self-emulsifying ester, ricinoleic acid, DOTP, Guerbet alcohol, ether carboxylic acid compounding agent, cardanol polyoxyethylene ether 5EO and cardanol polyoxyethylene ether 2EO into the above uniform and transparent liquid, and stir at 40°C until it is uniform and transparent to obtain a low-carbon biodegradable metalworking fluid. Mark it as 2# low-carbon biodegradable metalworking fluid for standby use.

[0039] Example 3

[0040] This embodiment is to prepare a low-carbon biodegradable metalworking fluid.

[0041] In percentage by mass, 6% of isopropanolamine, 3% of nano-silicon corrosion inhibitor, 5% of tricarboxylic acid rust inhibitor, 2.5% of benzotriazole, 10% of 182 self-emulsifying ester, 6% of ricinoleic acid, 4% of DOTP, 1% of Guerbet alcohol, 8% of ether carboxylic acid compounding agent, 5% of cardanol polyoxyethylene 5EO, 8% of cardanol polyoxyethylene ether 2EO, 0.6% of potassium hydroxide, and the balance is water.

[0042] Add water, isopropanolamine, tribasic acid, benzotriazole and potassium hydroxide into a 250ml beaker according to the above proportions, and stir at room temperature until it is uniform and transparent. Then add nano silicon anticorrosive agent, 182 self-emulsifying ester, ricinoleic acid, DOTP, Guerbet alcohol, ether carboxylic acid compounding agent, cardanol polyoxyethylene ether 5EO and cardanol polyoxyethylene ether 2EO to the above uniform and transparent liquid, and stir at 40°C until it is uniform and transparent to obtain a low-carbon biodegradable metalworking fluid. Mark it as 3# low-carbon biodegradable metalworking fluid for standby use.

[0043] Example 4

[0044] This embodiment is to prepare a low-carbon biodegradable metalworking fluid.

[0045] In percentage by mass, weigh 4% of isopropanolamine, 1% of nano-silicon corrosion inhibitor, 2% of tricarboxylic acid rust inhibitor, 0.5% of benzotriazole, 5% of 182 self-emulsifying ester, 4% of ricinoleic acid, 60% of DOTP, 4% of Guerbet alcohol, 2% of ether carboxylic acid compounding agent, 5% of cardanol polyoxyethylene 5EO, 6% of cardanol polyoxyethylene ether 2EO, 0.4% of potassium hydroxide, and the balance is water.

[0046] Add water, isopropanolamine, tribasic acid, benzotriazole and potassium hydroxide into a 250ml beaker according to the above proportions, and stir at room temperature until it is uniform and transparent. Then add nano silicon anticorrosive agent, 182 self-emulsifying ester, ricinoleic acid, DOTP, Guerbet alcohol, ether carboxylic acid compounding agent, cardanol polyoxyethylene ether 5EO and cardanol polyoxyethylene ether 2EO to the above uniform and transparent liquid, and stir at 40°C until it is uniform and transparent to obtain a low-carbon biodegradable metalworking fluid. Mark it as 4# low-carbon biodegradable metalworking fluid for standby use.

[0047] Example 5

[0048] This embodiment is a test of the hard water resistance and environmental protection performance of different metalworking fluids.

[0049] Two common metalworking fluids, semi-synthetic A model (Talent BCF 8008) and emulsion B model, were selected for comparative experiments with 1#-4# low-carbon metalworking fluids prepared in Examples 1-4 of the present invention. The factors used in the comparative experiments, such as pure water, nitrite, formaldehyde, mineral oil test method, tapping torque meter, filter paper, funnel, emulsion stability tester and experimental environment, were all kept consistent.

[0050] Different metalworking fluids were prepared into 5wt% concentration of 800ppm hard water to observe the hard water resistance, and then prepared into 5wt% tap water dilution to test the formaldehyde and nitrite content, as well as the mineral oil content and the original solution concentration (tested by refractometer). The test results are shown in Table 1.

[0051] Table 1 Test results of hard water resistance and environmental protection performance of different metalworking fluids

[0052]

[0053] The test results are shown in Table 1: In the same environment and the same test method, the hard water stability and test results of mineral oil and harmful substances of different types of metalworking fluids show that the hard water resistance of low-carbon metalworking fluids 1#-4# is better than that of semi-synthetic A type and emulsion B type, and does not contain mineral oil and harmful substances. Semi-synthetic A type metalworking fluid and emulsion B type metalworking fluid both have soap precipitation and contain mineral oil and harmful substances. This is the low-carbon metalworking fluid provided by the present invention, and its crude oil concentration content is basically maintained at the level of emulsion, without increasing the cost. It shows that the low-carbon biodegradable metalworking fluid of the present invention not only has excellent performance but is also environmentally friendly.

[0054] Example 6

[0055] This example is a test of the lubricity of different metalworking fluids.

[0056] Two common metalworking fluids, semi-synthetic type A (Talent BCF 8008) and emulsion type B, were selected for comparison experiments with the 1#-4# low-carbon metalworking fluids prepared in Examples 1 to 4 of the present invention.

[0057] Different metalworking fluids were prepared with tap water dilutions at a concentration of 10 wt %, and then the lubricity was tested using a tapping torque meter. The test results are shown in Table 2.

[0058] Table 2 Lubricity test results of different metalworking fluids

[0059] Metalworking fluid model Lubricity 1# Low carbon metalworking fluid 52.4Ncm 2# Low carbon metalworking fluid 51.3Ncm 3# Low carbon metalworking fluid 52.2Ncm 4# Low carbon metalworking fluid 52.1Ncm Semi-synthetic A type 68.8Ncm Emulsion B type 77.2Ncm

[0060] The test results are shown in Table 2. Under the same environment and the same test method, the test results of the lubrication performance of different types of metalworking fluids show that the 2# low-carbon metalworking fluid has the best lubricity, and the lubricity of the 1#-4# low-carbon metalworking fluids is better than the comparison agent A type and emulsion B type metalworking fluids. The results show that the low-carbon metalworking fluid has excellent lubricity, can meet demanding processing technology, and can achieve good processing effects at a lower concentration.

[0061] Example 7

[0062] This example is a test of different metalworking fluids on metal materials.

[0063] Two common metalworking fluids, semi-synthetic type A (Talent BCF 8008) and emulsion type B, were selected for comparison experiments with the 1#-4# low-carbon metalworking fluids prepared in Examples 1 to 4 of the present invention.

[0064] Different metalworking fluids were prepared into 5 wt% tap water dilutions, and the protective performance of each product on aluminum, copper and magnesium was tested in a 40°C constant temperature water bath test tank. The results are shown in Table 3.

[0065] Table 3 Test results of metal protection performance of different metalworking fluids

[0066] Metalworking fluid model Die-cast aluminum 7 Series Aluminum 6 Series Aluminum brass Magnesium Alloy 1# Low carbon metalworking fluid Level A Level A Level A Level A Level A 2# Low carbon metalworking fluid Level A Level A Level A Level A Level A 3# Low carbon metalworking fluid Level A Level A Level A Level A Level A 4# Low carbon metalworking fluid Level A Level A Level A Level A Level A Semi-synthetic A type Level A C-Class Level A C-Class C-Class Emulsion B type Class B C-Class Level A Level A C-Class

[0067] Note: Grade A is the best protection performance, indicating that the metal material has no discoloration or oxidation before and after immersion; Grade C is the worst, indicating that the metal material turns black, discolored and oxidized after immersion.

[0068] The results are shown in Table 2. Under the same environment and the same test method, the test results of different types of metalworking fluids show that 1#-4# low-carbon metalworking fluids have the best metal protection and can be used for processing a variety of different metal materials. Semi-synthetic A type and emulsion BB type metalworking fluids can only be used for processing one or two materials.

[0069] Example 8

[0070] This example is a test of the filterability of different metalworking fluids.

[0071] Two common metalworking fluids, semi-synthetic type A (Talent BCF 8008) and emulsion type B, were selected for comparison experiments with the 1#-4# low-carbon metalworking fluids prepared in Examples 1 to 4 of the present invention.

[0072] The above-mentioned different metalworking fluids were prepared into 5% concentrated dilutions, and the filterability of different metalworking industries was tested using filter paper and funnel.

[0073] Table 4 Filterability test results of different metalworking fluids

[0074] Metalworking fluid model Filterability 1# Low carbon metalworking fluid 158S 2# Low carbon metalworking fluid 155S 3# Low carbon metalworking fluid 157S 4# Low carbon metalworking fluid 158S Semi-synthetic A type 200S Emulsion B type 258S

[0075] The test results are shown in Table 4. Under the same experimental conditions, the filterability of 2# low carbon metalworking fluid is the best, and the filterability of 1#-4# low carbon metalworking fluids is better than that of semi-synthetic A type metalworking fluid and emulsion B type metalworking fluid.

[0076] As described above, the present invention can be well implemented. The above embodiments only describe the preferred implementation methods of the present invention, and do not limit the scope of the present invention. Without departing from the design spirit of the present invention, various changes and improvements made to the technical scheme of the present invention by ordinary technicians in this field should fall within the protection scope determined by the present invention.

Claims

1. A low-carbon biodegradable metalworking fluid, characterized in that: The low-carbon biodegradable metalworking fluid comprises, by mass percentage, 4%-6% of isopropanolamine, 1%-3% of nano-silicon anticorrosive agent, 2%-5% of tricarboxylic acid rust inhibitor, 0.5%-2.5% of benzotriazole, 5%-10% of 182 self-emulsifying ester, 4%-6% of ricinoleic acid, 40%-60% of DOTP, 4%-8% of Guerbet alcohol, 2%-4% of ether carboxylic acid compounding agent, 2%-5% of cardanol polyoxyethylene ether 5EO, 4%-8% of cardanol polyoxyethylene ether 2EO, 0.4%-0.6% of potassium hydroxide, and the balance is water.

2. The low-carbon biodegradable metalworking fluid according to claim 1, characterized in that: The low-carbon biodegradable metalworking fluid comprises, by mass percentage, 5% of isopropanolamine, 2% of nano-silicon corrosion inhibitor, 3% of tricarboxylic acid rust inhibitor, 1% of benzotriazole, 8% of 182 self-emulsifying ester, 5% of ricinoleic acid, 50% of DOTP, 6% of Guerbet alcohol, 3% of ether carboxylic acid compounding agent, 3% of cardanol polyoxyethylene ether 5EO, 5% of cardanol polyoxyethylene ether 2EO, 0.5% of potassium hydroxide, and the balance is water.

3. The method for preparing the low-carbon biodegradable metalworking fluid according to claim 1, characterized in that: The following steps are involved: Step 1: Weigh each component of the low-carbon biodegradable metalworking fluid according to its mass percentage. Step 2: Add water, isopropanolamine, tribasic acid, benzotriazole and potassium hydroxide into a 250 mL beaker and stir until uniform and transparent. Step 3: Add nano-silicon corrosion inhibitor, 182 self-emulsifying ester, ricinoleic acid, DOTP, Guerbet alcohol, ether carboxylic acid compounding agent, cardanol polyoxyethylene ether 5EO, and cardanol polyoxyethylene ether 2EO to the uniform transparent liquid prepared in step 2, and stir until uniform and transparent.

4. According to the method for preparing a low-carbon biodegradable metalworking fluid according to claim 3, the stirring temperature in the step 2 is room temperature.

5. According to the method for preparing a low-carbon biodegradable metalworking fluid according to claim 3, the stirring temperature in step 3 is 40°C.

6. Use of the low-carbon biodegradable metalworking fluid according to claim 1 in metal processing, wherein the metal is copper, aluminum and its alloys, magnesium and its alloys.

Citation Information

Patent Citations

  • Water-soluble lubricating liquid and aluminum cold rolling processing method

    CN111909769A

  • Micro-emulsified biodegradable metal working fluid with low carbon footprint as well as preparation method and application thereof

    CN113652294A

  • Method for producing polymer emulsion

    JP2012111816A